2009
DOI: 10.1016/j.jtcvs.2009.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patterns of relapse in thymic carcinoma and thymoma

Abstract: Objective Thymic carcinomas (TC) are considered to be more aggressive than thymomas and carry a worse prognosis. We reviewed our recent experience with the surgical management of thymic tumors and compared the outcomes and patterns of relapse between TC and thymoma. Methods Single institution retrospective cohort study. Data included patient demographics, stage, treatment, pathologic findings, and postoperative outcomes. Results During the period 1995–2006, 120 patients with thymic tumors underwent surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(67 citation statements)
references
References 26 publications
5
59
0
3
Order By: Relevance
“…Metastasis or recurrence occurred more frequently in high-risk thymomas (B2 and B3) than low-risk thymomas (A, AB, and B1). The results support the previously reported observations indicating more aggressive behaviours of thymic carcinomas compared to thymomas, as well as the association between oncological behaviour and the WHO histological classifications of thymic tumours 7, 21, 32 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Metastasis or recurrence occurred more frequently in high-risk thymomas (B2 and B3) than low-risk thymomas (A, AB, and B1). The results support the previously reported observations indicating more aggressive behaviours of thymic carcinomas compared to thymomas, as well as the association between oncological behaviour and the WHO histological classifications of thymic tumours 7, 21, 32 .…”
Section: Discussionsupporting
confidence: 92%
“…This finding is similar to the recent report of Ruffini et al , 31 which noted 24 cases of locoregional (including 12 pleural) recurrence among 47 thymic carcinoma patients, although the frequency of pleural involvement was higher in the present cohort. Lung metastasis was significantly more common in thymic carcinomas than in thymomas, as were the other sites of haematogenous spread, which supports the observations by Huang et al 21 in their prior study comparing thymomas and thymic carcinomas. Thoracic nodal involvement was noted in supraclavicular, para-oesophageal, retrocrural, pericardial, and axillary nodes; however, no other mediastinal or hilar nodes were involved, which contrasts the patterns of spread in other types of thoracic malignancy such as lung cancer.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with our results, Huang et al found differing patterns of relapse between patients with thymic carcinoma versus thymoma, with thymic carcinoma being associated with lower progression-free survival and higher rates of distant failures. 19 If complete or incomplete resection can be achieved, long-term survival rates have been as high as 60%–70% for those who receive adjuvant treatment. 68 A multimodality approach such as trimodality therapy or definitive concurrent chemoradiation in unresectable cases is recommended for thymic carcinoma regardless of disease stage.…”
Section: Discussionmentioning
confidence: 99%